2019
DOI: 10.3991/ijai.v1i1.10805
|View full text |Cite
|
Sign up to set email alerts
|

Gamification and Student Engagement with a Curriculum-based Measurement System

Abstract: <p>In this study, we employed a random control experiment to evaluate the effectiveness of gamification (e.g. scores, goal, progressive bar, etc.) and initial task difficulty on college student engagement in computer-based assessments. A group of Chinese college students (N=97) were randomly assigned to four groups obtained by crossing the two independent variables: gamification (with or without) and initial difficulty level (low or normal). The experiment lasted for 35 minutes, and each student was aske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Interactive games' performance measurements vary, leading to diverse research outcomes. For instance, a study by Yan (2019) used points and levels, while others used leaderboards and digital badges. Additionally, the appeal of games varies among age groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interactive games' performance measurements vary, leading to diverse research outcomes. For instance, a study by Yan (2019) used points and levels, while others used leaderboards and digital badges. Additionally, the appeal of games varies among age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Liang, 2021), as well as vocabulary (Rahimi et al, 2021) and grammar levels (R. Wang, 2022). Switching to another perspective, we could discover that different types of interactive technologies might exert a profound impact on language learning, such as flipped classroom models (C. Chen, 2015), games (Yan, 2019), and mobile applications (Tavassoli & Beyranvand, 2023). Though addressing positive potentials, the above studies cannot show us well-rounded results because they only focused on a specific aspect of language education or interactive technologies, thus we strongly need comprehensive meta-analysis tests to synthesize all the results.…”
Section: Backgrounds Of Interactive Technologies Used In Language Edu...mentioning
confidence: 99%
See 1 more Smart Citation
“…Schols, M. [17] found four factors that encourage teachers and educators to participate in technological learning. Yan, Y., et al [18] indicated that cognitive engagement of learners can be promoted through game-based teaching mode.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…In the eighth and final article, Yu Yan, Simon Hooper and Shi Pu [8] present a study in which they have use learning analytics methods in order to evaluate the effectiveness of gamification and initial task difficulty on college student engagement with computer-based assessments.…”
Section: Overview Of Papers In the First Issuementioning
confidence: 99%